Genetic improvement in coffee (Coffea arabica L.) cultivation: Methodological advances and application proposal using traditional methods and biotechnological tools - Cardoza Sánchez, Alan Mike (2025)
Coffee is a very important crop both nationally and globally, with Peru being the leading exporter of organic coffee, is native to Africa, and the most important species is Coffea arabica. The objective of this work was to carry out a literature review about the germplasm used and the genetic improvement methods used in coffee cultivation, with the purpose of proposing an improvement scheme that includes the application of traditional methods and biotechnological tools for improvement of coffee cultivation. Information from genetic improvement programs in Brazil, Colombia and Central America and other institutions dedicated to the management, research and commercialization of coffee cultivation was used. The most used methods for genetic improvement are Pedigree, backcrossing and the production of F1 hybrids through somatic embryogenesis. In Brazil, Colombia and other countries, molecular markers are being used to develop cultivars with rust resistance in a shorter period. Finally, the breeding strategy to be implemented is the pyramiding of genes for rust resistance using molecular markers. This strategy consists of introgressing the SH3 gene present in the C. liberica species into the catimor cultivar, which is highly productive and has the rust resistance genes SH6, SH7, SH8 and SH9. This proposal is of great importance in countries like Peru, where coffee represents a strategic export product. Breeding schemes that incorporate gene pyramiding using molecular markers not only improve the efficiency of selecting cultivars with resistance to coffee rust but can also accelerate breeding programs by reducing lengthy phenotypic evaluation cycles. In practice, this could translate into more productive cultivars that are resistant to biotic and abiotic factors and adapted to different types of environments. This would mark a new stage in coffee genetic improvement in Peru, based on precision agriculture and sustainability.